Morphological and Morphometrical Studies on the Radius and Ulna of Himalayan Mongoose - Shukla P; Rajput R; Pathak V; Gupta D (Indian Journal of Veterinary Anatomy, 2025)
The present study was carried out on the radius and ulna of Himalayan mongoose, a brown mongoose species which is native to the Himalayan region of Indian subcontinent. The specimen under study was collected from an animal that was hit by a moving car in Palampur. The specimen was preserved and the dissection was done to record the gross anatomical observations on the radius and ulna of Himalayan mongoose. The radius and ulna were long bones of the forearm region and were straight. The interosseous space extended along the length of the bone. The shaft of the radius was slightly curved. Proximal extremity had an ovoid articular surface. The bicipital tuberosity was present on the proximal part towards the lateral border. Distally it had a styloid process on the medial side. Ulna was longer and heavier than radius. Proximal extremity had olecranon process, anconeus process and a trochlear notch.